Insights Into the Role of Heat Shock Protein 27 in the Development of Neurodegeneration - Holguin, Bianka A.; Hildenbrand, Zacariah L.; Bernal, Ricardo A. (Frontiers in Molecular Neuroscience, 2022)
Small heat shock protein 27 is an intrinsically disordered, yet critically important chaperone, that plays a key role in several essential and varied physiological processes. These include thermotolerance, apoptosis, cytoskeletal dynamics, cell differentiation, protein folding, among others. Despite its relatively small size and intrinsic disorder, it forms large and polydisperse oligomers that are in equilibrium with dimers. This equilibrium is driven by transient interactions between the N-terminal region, the α-crystallin domain, and the C-terminal region. The continuous redistribution of binding partners results in a conformationally dynamic protein that allows it to adapt to different functions where substrate capture is required. However, the intrinsic disorder of the amino and carboxy terminal regions and subsequent conformational variability, has made structural investigations challenging. Because heat shock protein 27 is critical for so many key cellular functions, it is not surprising that it also has been linked to human disease. Charcot-Marie-Tooth and distal Hereditary Motor Neuropathy are examples of neurodegenerative disorders that arise from single point mutations in heat shock protein 27. Development of possible treatments, however, depend on our understanding its normal function at the molecular level so we might be able to understand how mutations manifest as disease. This review will summarize recent reports describing investigations into the structurally elusive regions of Hsp27. Recent insights begin to provide the required context to explain the relationship between a mutation and the resulting loss or gain of function that leads to Charcot-Marie Tooth disease and distal Hereditary Motor Neuropathy.